Possible connections between health equity and primary health care: a scoping review - Ana Júlia Nociti Lopes Fernandes; Luciana Cisoto Ribeiro; Janise Braga Barros Ferreira (BMC Public Health)
Abstract According to the literature, primary health care plays a major role in the dissemination and operation of the principle of health equity. The study investigated how health equity is connected with primary care and public health policies in the national and international literature. Searches were made in the SCOPUS, CINAHL, BVS, PubMed, and Scielo databases, using the method proposed by the Joanna Briggs Institute. The eligibility criteria were developed based on the strategy Population (population in general), Concept (health equity), and Context (PHC). Overall, 34 materials were included in the study. Equity was mainly associated with Whitehead’s theoretical conceptions, focusing on access, marginalized groups, and abstract principles and values. Connections were found in the spheres of the micro-space of health work, management, and policies. Few materials measured equity, within the aspects of access, care, funding, and outcomes. The concept was mostly used in its negative connotation and in relation to the equality/inequality binomial. The relationship between equity and primary care was developed in the fields of micro-processes, macro-processes, and health results. It was concluded that there is a need for the development of specific instruments to measure the concept and for greater clarity in publications on the topic.